PENGARUH PEMBERDAYAAN DAN MOTIVASI KERJA DENGAN MEDIASI KOMITMEN ORGANISASIONAL TERHADAP KINERJA GURU ( STUDI KASUS DI YAYASAN PENDIDIKAN NASIONAL PATI ) SRI KARTINI (Jurnal Mahasiswa Pasca Sarjana, 2014)
The purpose of this study was to determine the effect of empowerment on organizational commitment and performance of educators, organizational comitment and motivation to the performance of educators, organizational comitment to the performance of educators, the indirect effect on the performance of the empowerment and motivation of  teachers organizational commitment mediated. Location of the study conducted at the National Education Foundation Pati2014 . The number of samples in this study were 101 respondents and include research or census population. The method of analysis is qualitative and quantitative. Quantitative analyzes were performed using multiple regression test to test the hypothesis that the level of significance set at 5 %. To analyze the models with SPSS 16.0 .. The results showed that the direct effect of empowerment for (0.200) on the performance of educators and of (0.414) to organizational commitment, motivation for (0.108) affect the performance of educators and by (0.512) the organizational commitment, organizational commitment for (0.716) affect the performance of educators . Empowerment indirectly affect the performance of (0.296) educators, while the effect of motivation on the performance of (0.367) educators mediated organizational commitment. The results of this study can be used by future researchers as materials science research in the field of organizational behavior science or the like. Keywords:       teacher empowerment, work motivation, organizational co  mitment and performance of teachers.